2000
DOI: 10.1063/1.1287127
|View full text |Cite
|
Sign up to set email alerts
|

Photoionization spectroscopy of traps in GaN metal-semiconductor field-effect transistors

Abstract: Measurements of the spectral and intensity dependences of the optically-induced reversal of current collapse in a GaN metal-semiconductor field-effect transistor ͑MESFET͒ have been compared to calculated results. The model assumes a net transfer of charge from the conducting channel to trapping states in the high-resistivity region of the device. The reversal, a light-induced increase in the trap-limited drain current, results from the photoionization of trapped carriers and their return to the channel under t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 32 publications
1
47
0
Order By: Relevance
“…The spectral dependence of this absorption-the photoionization spectrum -is characteristic of a deep center, and can be employed as a signature of the relevant trap. Measurement of the spectral dependence of this lightinduced drain current increase in a GaN metalsemiconductor FET ͑MESFET͒ was shown 7,8 to generate an absorption spectrum reflecting the existence of two distinct trap species. These results have been recently verified independently by other workers.…”
Section: Introductionmentioning
confidence: 99%
“…The spectral dependence of this absorption-the photoionization spectrum -is characteristic of a deep center, and can be employed as a signature of the relevant trap. Measurement of the spectral dependence of this lightinduced drain current increase in a GaN metalsemiconductor FET ͑MESFET͒ was shown 7,8 to generate an absorption spectrum reflecting the existence of two distinct trap species. These results have been recently verified independently by other workers.…”
Section: Introductionmentioning
confidence: 99%
“…4,5,8 Activation energies of deep traps responsible for the current collapse were studied by optical and thermoexcitation methods. 6,7 The surface passivation approach was suggested to increase the microwave output power. 9,10 However, although the current collapse phenomenon seems to be general for different types of GaNAlGaN FETs, as well as for GaAs power FETs, both the concrete mechanism of rf output power suppression and physical locations of the carrier trapping centers responsible for the collapse, are still far from clear.…”
Section: Mechanism Of Radio-frequency Current Collapse In Gan-algan Fmentioning
confidence: 99%
“…The phenomenon responsible for this degradation is generally referred as ''rf-current collapse'' or ''current slump,'' which recently has been a subject of several studies. [4][5][6][7][8][9] Drain currents under large input drives were measured showing significant current compression compared to the dc values. 4,5,8 Activation energies of deep traps responsible for the current collapse were studied by optical and thermoexcitation methods.…”
Section: Mechanism Of Radio-frequency Current Collapse In Gan-algan Fmentioning
confidence: 99%
“…We must conclude, therefore, that the 3.7 eV threshold does not appear to be associated with a deep centre that could result in current collapse, but instead corresponds to the photoneutralisation of ionised shallow acceptors. Since the trap1 defect and the 3.7 eV threshold were the only features in the photoionisation spectrum that could be associated with the collapse, it appears that the sole trapping centre that is responsible for stressinduced current collapse in MBE-grown HEMTs is trap1, a GaN buffer layer defect [3,4].…”
mentioning
confidence: 99%
“…The dependence of the drain current increase on the incident photon energy maps out a photoionisation spectrum, which is an absorption spectrum that is characteristic of the deep defect and may be used to identify or 'tag' the defect. Previous photoionisation studies of nitride-based metal-semiconductor field effect transistors (MESFETs) [3][4][5] and high electron mobility transistors (HEMTs) [6] grown by metal organic chemical vapour deposition (MOCVD) have shown that two deep traps residing in the highresistivity (HR) GaN buffer layer are responsible for collapse in these devices. The two traps, labelled trap1 and trap2, introduce two broad, below-gap absorptions into the spectrum with photoionisation thresholds at 1.8 and 2.85 eV, respectively.…”
mentioning
confidence: 99%